2021
DOI: 10.3390/metabo11110728
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between Isobaric Ions Using Microdroplet Hydrogen–Deuterium Exchange Mass Spectrometry

Abstract: Isobaric ions having the same mass-to-charge ratio cannot be separately identified by mass spectrometry (MS) alone, but this limitation can be overcome by using hydrogen–deuterium exchange (HDX) in microdroplets. Because isobaric ions may contain a varied number of exchangeable sites and different types of functional groups, each one produces a unique MS spectral pattern after droplet spray HDX without the need for MS/MS experiments or introduction of ion mobility measurements. As an example of the power of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…For instance, when studying pharmaceutical compounds using MS, the oxidized peak may be incorrectly assigned to drug metabolites that are isomeric or structurally identical to the oxidized product . In addition to conventional qualitative analysis, ambient ionization techniques have been incorporated into hydrogen/deuterium exchange MS in several previous studies. Overlapping signals corresponding to oxidized species and partially deuterated species would negatively impact the accuracy of determining the deuterium uptake number . In light of these issues, it is crucial to identify feasible approaches to eliminate oxidation from MS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, when studying pharmaceutical compounds using MS, the oxidized peak may be incorrectly assigned to drug metabolites that are isomeric or structurally identical to the oxidized product . In addition to conventional qualitative analysis, ambient ionization techniques have been incorporated into hydrogen/deuterium exchange MS in several previous studies. Overlapping signals corresponding to oxidized species and partially deuterated species would negatively impact the accuracy of determining the deuterium uptake number . In light of these issues, it is crucial to identify feasible approaches to eliminate oxidation from MS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A relatively confident result for an ion identification could be assured by chemometrics based on multiple matching criteria, including exact mass tolerance, isotope abundance, adduct ion types, and featured fragments [117][118][119]. Apart from the post-acquisition dry method, the online wet experiments also provide complementary chemical structure to help isobaric ion differentiation, such as hydrogen-deuterium exchange (HDX) during the ionization process in the liquid phase or and post-ionization traveling process in the gas phase [120,121].…”
Section: Prospective Outlookmentioning
confidence: 99%
“…Coupling of wristband technology with HR‐MS can enable the evaluation of environmental contaminates, screen unexpected chemical exposures, and capture information about pesticides, flame retardants, polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs) [27] . We previously used polymer‐based spray ionization mass spectrometry for the metabolomic and lipidomic profiling of biological fluid samples [17,22–26] . It has advantages in rapid screening and in vitro diagnosis of disease, identification of discriminative biomarkers and dysregulated pathways, and even illumination of gene‐environment interactions, and disease‐relevant genomic regions [28] …”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Recent studies demonstrated that polymer-based spray ionization coupled with high-resolution mass spectrometry (HR-MS) provides a promising approach for molecular and metabolic profiling and quantitation of biological fluids. [16][17][18][19][20][21][22][23][24][25][26] Coupling of wristband technology with HR-MS can enable the evaluation of environmental contaminates, screen unexpected chemical exposures, and capture information about pesticides, flame retardants, polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs). [27] We previously used polymerbased spray ionization mass spectrometry for the metabolomic and lipidomic profiling of biological fluid samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation